Influence of citric acid on the physical and biomineralization ability of freezethaw poly(vinyl alcohol) hydrogel - Abdul Wahid, Mohamad Nizam; Abd Razak, Saiful Izwan; Abdul Kadir, Mohammed Rafiq; Hassan, Rozita; Mat Nayan, Nadirul Hasraf; Mat Amin, Khairul Anuar (SAGE Publications, 2018)
This work reports the modification of freeze/thaw poly(vinyl alcohol) hydrogel using citric acid as the bioactive molecule for hydroxyapatite formation in simulated body fluid. Inclusion of 1.3 mM citric acid into the poly(vinyl alcohol) hydrogel showed that the mechanical strength, crystalline phase, functional groups and swelling ability were still intact. Adding citric acid at higher concentrations (1.8 and 2.3 mM), however, resulted in physically poor hydrogels. Presence of 1.3 mM of citric acid showed the growth of porous hydroxyapatite crystals on the poly(vinyl alcohol) surface just after one day of immersion in simulated body fluid. Meanwhile, a fully covered apatite layer on the poly(vinyl alcohol) surface plus the evidence of apatite forming within the hydrogel were observed after soaking for seven days. Gel strength of the soaked poly(vinyl alcohol)/citric acid-1.3 mM hydrogel revealed that the load resistance was enhanced compared to that of the neat poly(vinyl alcohol) hydrogel. This facile method of inducing rapid growth of hydroxyapatite on the hydrogel surface as well as within the hydrogel network can be useful for guided bone regenerative materials.